The Effect OfLumbricusrubellus With Different Frequency On Growth And Survival Of Larvae Siban(Cyclocheilicthysapagon) - Yolanda Puspita; Nuraini Nuraini; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted on Maret - April 2018 in the Laboratory of Fish Hatchery and Breeding Faculty of Fisheries and Marine Sciences, University of Riau.The purpose of this research was to Effect OfLumbricusrubellus With Different Frequency On Growth And Survival Of Larvae Siban (Cyclocheilicthysapagon. This research used the experimental method, while the experimental design using completely randomized design (CRD) with 4 treatments, each with 3 replication.The composition of the treatment P1 frequency the provision of feed 3 times a days , treatment P2 frequency the provision of feed 4 times a day, treatment P4 frequency the provision of feed 5 times a days, treatment P4 frequency the provision of feed 6 times a day. The best result of the treatments from this research frequency of the feed about 6 times a daygrow with0,26 g (weight),  2,60cm (length)and 6,43% per days (Specific growth rate). Statistical test results show that the survival rate of larvae  Cyclocheilicthysapagon has no significant effect on all treatments.The water quality parameters during this research were: temperature 25,6-28,2oC, pH 5-6,8, dissolved oxygen 5-6,5 mg/l.Key words: Cyclocheilicthysapagon, Lumbricus rubellus,  frequency, growth and survival